Turkey: An emerging global arms exporter. Growing competitiveness and strategic recalibration of the Turkish defence industry - Jens Bastian (Stiftung Wissenschaft und Politik (SWP), 2024)
Over the past decade, Turkey's defence industry has undergone rapid development and its products have repeatedly proved their military capability. The Bayraktar-TB2 drone - a product of the Turkish manufacturer Baykar - is exported to numerous countries. In Ukraine, it is being used extensively against the Russian army. In Nagorno-Karabakh, it turned out to be a game changer in favour of Azerbaijan in the conflict with Armenia. And it has left its mark on the battlefields of Syria as well as in northern Iraq and Libya. But the TB2 drone is only the most visible sign of what is a new era for Turkey's defence policy. The innovation ecosystem that has emerged in the Turkish military-industrial complex is intended to position the country as a 'teknonation'. For Turkey's NATO partners, this recalibration presents strategic challenges for further cooperation with Ankara.
Keywords: 320; Turkey's defence industry; Bayraktar-TB2 drone; NATO; Nagorno-Karabakh